2017
DOI: 10.1038/srep40779
|View full text |Cite
|
Sign up to set email alerts
|

Clinical variations in Parkinson’s disease patients with or without REM sleep behaviour disorder: a meta-analysis

Abstract: This study aimed to evaluate the clinical variations in patients with Parkinson’s disease (PD) with (PDRBD) or without REM sleep behaviour disorder (RBD) (Non-RBD), and PDRBD patients were classified into Confirmed-RBD (definite diagnosis with polysomnography, PSG) and Probable-RBD (without PSG re-confirmation). The clinical difference between the groups of patients was measured as an odds ratio (OR) or standardized mean difference (SMD, Cohen d). A total of 31 articles with data from 5,785 participants were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 57 publications
1
20
0
Order By: Relevance
“…The PD-MCI group was older and contained a larger proportion of patients with bilateral parkinsonism, and most had probable RBD. This combination of features may signal a rapidly progressive subtype of PD (22,28). The fact that such more severely affected PD patients have higher subject scores on both the PDRP and the iRBDRP again suggests that both patterns are markers of severity of the same disease process.…”
Section: Discussionmentioning
confidence: 96%
“…The PD-MCI group was older and contained a larger proportion of patients with bilateral parkinsonism, and most had probable RBD. This combination of features may signal a rapidly progressive subtype of PD (22,28). The fact that such more severely affected PD patients have higher subject scores on both the PDRP and the iRBDRP again suggests that both patterns are markers of severity of the same disease process.…”
Section: Discussionmentioning
confidence: 96%
“…However, there remains a question about whether treatment responses in trials applied exclusively to this patient population will be generalizable because RBD appears to predict a certain subtype of PD. In a recent meta‐analysis, RBD was observed more frequently in male patients, elderly patients, patients with longer disease duration, and patients with greater motor impairment . This builds on work showing that RBD patients had less tremor, more falls, and were less responsive to levodopa .…”
Section: Parasomniasmentioning
confidence: 77%
“…In a recent meta-analysis, RBD was observed more frequently in male patients, elderly patients, patients with longer disease duration, and patients with greater motor impairment. 35 This builds on work showing that RBD patients had less tremor, more falls, and were less responsive to levodopa. 36,37 Others have suggested that RBD is a risk factor for mild cognitive impairment 38 and later dementia.…”
Section: Rem Parasomniasmentioning
confidence: 93%
“…The diagnosis of RBD can be based on a questionnaire or clinical manifestations without confirmation by polysomnography (PSG) [2,13,14].Therefore, a detailed history of complex motor behaviors and vocalizations during REM sleep is very important for a clinical diagnosis of RBD. However, for the objective diagnosis of RBD, complex motor behaviors during REM sleep and the presence of REM sleep without atonia should be confirmed by PSG [11].…”
Section: Diagnosis Of Rbd In Pdmentioning
confidence: 99%
“…PSG can detect increased chin muscle tone (i.e., absence of atonia) by the submental EMG or increased phasic muscle activity by the limb EMG during REM sleep [2,15]. Thus, PSG is not required for the clinical diagnosis of RBD [13,14]. It has been reported that a total score of 6 or Sleep Disorders in Parkinson's Disease http://dx.doi.org/10.5772/intechopen.73520 higher obtained from 'the RBD screening questionnaire (RBDSQ)' used for the clinical diagnosis of RBD may strongly support (sensitivity = 0.842, specificity = 0.962) the diagnosis [16].…”
Section: Diagnosis Of Rbd In Pdmentioning
confidence: 99%